The Effect of Sharia Principles in Banking on Customer Satisfaction (Study Case: Shiraz Sepeh Bank) - Fereshte Nafar; Poya Abolhasani; Amirhossein Khataei Dayeni (تحقیقات مالی اسلامی (پیوسته))
Financial performance in banking relies on maintaining long-term relationships with customers and the reason for that is the nature of the products and services it offers. Considering that Islamic banking is one of the growing service industries in Islamic countries, it is very important to investigate the effect of compliance with the principles of Sharia on the satisfaction of bank customers in the financial process. The main purpose of this research is to investigate the effect of Islamic Sharia compliance on customer satisfaction in the financial process of Sepeh Shahr Bank, Shiraz. In this research, using the existing theoretical literature, and according to the goal of the researcher, out of 5 variables Sharia compliance in deposit, Sharia compliance in investment, Sharia compliance in auditing, Sharia compliance in products and services, and also customers' awareness of Islamic principles of financial processes were used. Then, using the structural equation sampling method, 110 people were selected as a sample. Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) was used to analyze the data, research model, and test the proposed hypotheses. The results of the test of research hypotheses showed that the application of Sharia in general has a significant effect on the satisfaction of bank customers. In examining the research hypotheses regarding the impact of each of the desired variables, the results indicate that among these 5 variables, Sharia compliance in auditing with a beta path coefficient (0.315) has a greater impact on customer satisfaction. This indicates the importance of Shari'a auditing committees at the level of banks. After that, compliance with Sharia in deposit with beta path coefficient (0.299) has an impact on customer satisfaction, and in this sense, it is of secondary importance.